Factors Affecting Knowledge and Adoption of Preventive and Control Measures of Diseases among Goat Owners under Field Condition (Indian Journal of Extension Education, 2018)
Disease prevention is more economical than treatment and some diseases cannot be treated. Considering this factor the present study was taken up with the objective to assess knowledge and adoption level of preventive and control measures of diseases and factors affecting in knowledge and adoption among goat owners under field condition. The study was purposively conducted in West Bengal and Uttar Pradesh on the basis of high goat populated state in the country. In all, 180 respondents were randomly selected for the study. The study shows that majority of the respondents had knowledge of keeping feed and water trough clean and had adopted this practice. Disinfection of shed at least once in a week and isolation of healthy animals from sick animals was not known to majority of the respondents and therefore majority had not adopted this practice. Vaccination as preventive and control measure of diseases in goat was known to majority of the respondents even through the adoption of this practice was low. Proper disposal of carcass and litter was known to majority of the respondents thereby majority had fully adopted these practices. None had knowledge on quarantine of newly purchased animals, use of footbath and rotational grazing and thus adoption to these practices were nil. The study also shows that goat owners had medium level of knowledge but had low level of adoption. The study revealed that education, flock size, farming experience, mass media exposure, formal interpersonal contact and social participation had significant and positive association with knowledge level similarly education, family education status, knowledge level, mass media exposure, formal interpersonal contact and social participation had significant and positive association with adoption. The study further revealed that education and farming experience of the respondents were main contributing factors for knowledge level in preventive and control measures of diseases and knowledge level, mass media exposure, income in goat farming and annual family income were the main contributing factors in adoption of preventive and control measures of diseases.